2021
DOI: 10.1002/adma.202100221
|View full text |Cite
|
Sign up to set email alerts
|

A Stretchable and Transparent Electrode Based on PEGylated Silk Fibroin for In Vivo Dual‐Modal Neural‐Vascular Activity Probing

Abstract: Transparent electrodes that form seamless contact and enable optical interrogation at the electrode–brain interface are potentially of high significance for neuroscience studies. Silk hydrogels can offer an ideal platform for transparent neural interfaces owing to their superior biocompatibility. However, conventional silk hydrogels are too weak and have difficulties integrating with highly conductive and stretchable electronics. Here, a transparent and stretchable hydrogel electrode based on poly(3,4‐ethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 71 publications
0
84
0
1
Order By: Relevance
“…Wearable devices have attracted emerging attention in recent years due to their excellent interactivity with the human body and the ability for long-term monitoring, which are therefore widely applied in the monitoring of small human motions, [1,2] large body movements, [3,4] and biochemical detection. [5,6] As required by the flexibility and sensitivity of wearable devices, soft materials such as elastomers and hydrogels are commonly employed as the skeletons of flexible devices, while carbon nanotubes (CNTs), graphene, conductive polymers, and other structural color-based composite hydrogel was fabricated with the above silica PCs.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable devices have attracted emerging attention in recent years due to their excellent interactivity with the human body and the ability for long-term monitoring, which are therefore widely applied in the monitoring of small human motions, [1,2] large body movements, [3,4] and biochemical detection. [5,6] As required by the flexibility and sensitivity of wearable devices, soft materials such as elastomers and hydrogels are commonly employed as the skeletons of flexible devices, while carbon nanotubes (CNTs), graphene, conductive polymers, and other structural color-based composite hydrogel was fabricated with the above silica PCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a stretchable silk hydrogel electrode based on PEGylated SF and PEDOT:PSS has also been reported by Cui et al. [ 165 ]. It demonstrated that the PEGylated silk protein with poly(ethylene glycol) diglycidyl ether (PEGDE) had significantly improved the Young's modulus and stretchability of the hydrogel compared to traditional silk hydrogel, and hence realized a stretchable, nontransient, and relative stable conformal electronic for neural activity characterization [ 165 ].…”
Section: Advanced Biomedical Applications Of Rsf Materialsmentioning
confidence: 77%
“…During this period, a small amount of solution was dropped on the activated silicon wafer every 12 h and left to stand overnight in a dry and clean area. After the water was fully evaporated and dried, the silicon wafer containing the sample was pasted on the electron microscope sample stage with a conductive adhesive, and gold was sprayed with a spray current of 30 mA in a vacuum state for 2 min [ 41 ]. The microscopic morphology of the sample surface was observed under a scanning electron microscope (Nova NanoSEM 450, Hillsboro, OR, USA) with a shooting voltage of 15 kV.…”
Section: Methodsmentioning
confidence: 99%